Collocation of restorative justice with human rights in Indonesia - Ismail, Dian Ekawaty; Arsyad, Yusna; Ahmad, Ahmad; Nggilu, Novendri M.; Yassine Chami (Faculty of Law, University of Muhammadiyah Malang, 2024)
Applying restorative justice in Indonesia is beset by obstacles like a lack of knowledge, inadequate infrastructure, and opposition from law enforcement, especially when human rights considerations are incorporated into the process. For this reason, the relationship between these two elements is worth examining. This paper explores and analyses the integration or synthesis of restorative justice with human rights in Indonesia. This paper employs a normative approach with prescriptive analysis based on studies of legislation and cases that integrate the principles of restorative justice with human rights. The findings indicate that collocation helps understand how grammatical structures can reflect and influence the interpretation of restorative justice in human rights, particularly in legal texts and policy reports. In Indonesia, restorative justice can be used in conjunction with the enforcement of human rights laws, particularly when addressing grave human rights breaches, since it emphasizes balanced reconciliation, recovery, and reintegration between offenders, victims, and society. In conclusion, although it has several implementation and legal issues, restorative justice can be an alternate strategy for resolving grave human rights breaches. The recommendations are for a stronger and more comprehensive legal framework to support the implementation of restorative justice in Indonesia's human rights context.